Are gender-diverse banks less risk-averse? Evidence from the Kenyan commercial banks - Rogers Ochenge (Kenya Bankers Association (KBA), 2024)
This paper examines the effect of board gender diversity on bank risk. The empirical analysis is conducted using 21 sample Kenyan commercial banks during the period 2010-2022 in a panel regression framework. Two key results are documented: first, that the share of women in Kenyan bank boards is low (sample average of about 19%), although it has made progress, rising from about 13% in 2010 to about 26% by end of 2022. Second, the paper provides evidence that increasing women directors in banks' boards, curtails excessive bank risk-taking and promotes bank stability. Thus, regulators may consider imposing gender quotas in bank boards as a way of mitigating bank risk.
Keywords: 330; Risikoaversion; Bank; Board of Directors; Frauen; Weibliche Führungskräfte; Diversity Management; Kenia